Development of prototypes of passive protective orthoses through additive manufacturing - Marín-Brenes, José Fabián (2024)
Additive manufacturing has revolutionized production by enabling the creation of objects from digital models, without requiring molds. In the medical field, customization takes on crucial importance, with 3D printing serving as an effective vehicle for orthosis creation. The significance of customization lies in the limitation of generic devices, which may prove inadequate for certain patients and lack aesthetic appeal. The findings of the study reveal that 3D printing and scanning play a fundamental role in optimizing orthosis production processes, generating highly personalized and ergonomic structures. Medical professionals consulted to validate the prototypes deem them viable. However, there arises a need to enhance device safety and functionality, particularly when considering potential volume changes in injuries during treatment. A detailed cost analysis uncovers that labor constitutes most of the manufacturing cost, accounting for 73.87%. It is followed by the filament used, at 23.14%, Velcro at 1.4%, and finally, consumed electricity at 1.59%.